Self-Efficacy, Satisfaction, and Academic Achievement: The Mediator Role of Students' Expectancy-Value Beliefs - Doménech-Betoret, Fernando; Abellán-Roselló, Laura; Gómez-Artiga, Amparo (Frontiers in Psychology, 2017)
Although there is considerable evidence to support the direct effects of self-efficacy beliefs on academic achievement, studies that have explored the motivational mechanism which mediates the self-efficacy-achievement relationship are scarce, but are necessary to understand how and why self-efficacy affects students’ academic achievement. Based on a socio-cognitive perspective of motivation, this study examines the relationships among academic self-efficacy, students’ expectancy-value beliefs, teaching process satisfaction and academic achievement. Specifically, its main aim is to identify some motivational-underlying processes through which students’ academic self-efficacy affects student achievement and satisfaction. Student achievement and satisfaction are two of the most important learning outcomes, and are also considered key indicators of education quality. The sample comprises 797 Spanish secondary education students from 36 educational settings and three schools. The scales that referred to self-efficacy and expectancy-value beliefs were administered at the beginning of the course, whereas student satisfaction and achievement were measured at the end of the course. The data analysis was conducted by structural equation modeling (SEM). The results revealed that students’ expectancy-value beliefs (Subject value, Process expectancy, Achievement expectancy, Cost expectancy) played a mediator role between academic self-efficacy and the achievement/satisfaction relationship. These results provided empirical evidence to better understand the mechanism that mediates self-efficacy-achievement and efficacy-course satisfaction relationships. The implications of these findings for teaching and learning in secondary education are discussed.